The Effect Of Work Motivation And Work Discipline On The Performance Of Employees Of The Population And Civil Registration Office (Dukcapil) Of Serang Regency - Alam, Surya; Wijaya, Priatna (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
The purpose of this study is to determine the Effect of Work Motivation and Work Discipline on the Performance of Employees of the Population and Civil Registration Service (Dukcapil) of Serang Regency.This research uses a quantitative approach method. The population in this study was all employees of the Population and Civil Registration Service (Dukcapil) of Serang Regency totaling 58 people. While the method is simple random sampling because the sampling of members from the population is carried out randomly without paying attention to the strata in the population. In this study, the author used the saturated sampling technique is a sample determination technique when all members of the population are used as samples. Based on the description above, the population as well as the sample used in this study were 58 samples at the Population and Civil Registration Service (Dukcapil) of Serang Regency.The results of the analysis of the first hypothesis there is a significant influence between work motivation on employee performance obtained ttable of 2,002 while tcount of 4,017 then work motivation (X1) on employees (Y) in the t test, obtained results tcount > ttable (4.017 > 2,002) with a significance level of 0.00 (0.00 > 0.05), ttable of 2,002 while t counts 4,356 then work discipline (X2) on employee performance (Y) in the t test, obtained the results of t count > ttable (4,356 > 2,002) with a significance level of 0.00 (0.00 > 0.05) and Fcount = 26.016 while the value of Ftable (df = n – k – 1 = 58-2-1=55) of 3.160 with a real level of 0.05. F counts > Ftable (26,016 > 3,160) thus H0 is rejected and H1 is accepted which means there is a significant influen The conclusion of this study in hypothesis one has a significant influence of work motivation on employee performance, hypothesis two has a significant influence of work discipline on employee performance, and hypothesis three has a significant influence of work motivation and work discipline on employee performance